Comparison of Clinical Outcome of Laparoscopic with Open Repair Surgery for Duodenal Ulcer Perforation - Dileep Kumar, Muhammad Tahir Ali, Shahid Hussain Mirani, Muhammad Hanif Memon, Abdul Rasheed Zai, Khalid Abaidullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the clinical outcome of laparoscopic versus open repair of perforated peptic ulcer. Study Design: Comparative analytical study Place and Duration of Study: Department of Surgery Ward-2, Jinnah Postgraduate Medical Centre Karachi from 1st March 2021 to 28th February 2022. Methodology: Fifty patients with duodenal ulcer perforation were divided into two equal groups and open surgery or laparoscopic was performed after clinical examination. Boeys score, Mannheim Peritonitis Index preoperatively and VAS scoring as post-operative was done. Results: There were more males than females within both groups with a mean age of 51.3±16.5 years in group I and 55.7±14.9 years in group II. The perforation size of group I was greater as 16.3±6.4 mm than group II patients which were 15.9±5.7 mm. The post-operative complications showed a high frequency of respiratory cardiovascular and surgical site complications with greater mortality rate in Group II A major decrease in pain score was recorded in laparoscopic group such as group I in comparison with open repair such as group II. Conclusion: Shorter hospitalization and less post-operative pain was observed in laparoscopic repair for perforated peptic ulcer as compared to open-repair surgery.